The impact of organic loading on the anaerobic digestion of cow manure: Methane production and kinetic analysis - Tariq Alkhrissat (Case Studies in Chemical and Environmental Engineering, 2024)
The efficacy of methane production through anaerobic digestion is influenced by organic loading. The primary objective of this research was to examine the impact of organic loading on the anaerobic mesophilic digestion of cow manure (CM). Additionally, the study aimed to analyze the many parameters associated with the digestion process and assess the kinetics involved. The present study aimed to evaluate the anaerobic digestion of CM under various organic loading conditions, namely at loading rates of 20, 25, 30, 35, and 40 gVS/L. The methane output of CM was shown to rise with an increase in organic loading. The maximum cumulative methane production was recorded at a substrate concentration of 40 gVS/L, resulting in a methane yield of 125.98 LCH₄/KgVS. Furthermore, the modified Gompertz model and Logistic model equation, which exhibited an R2 value of 0.994 and 0.991, respectively, exhibited robust consistency and a high level of agreement between the anticipated and experimental results. The addition of a large number of substrates to the systems with an increase in organic loading resulted in an increase in λ and a slowdown of nutrient transport and hydrolysis processes.